PEMBERLAKUAN HUKUM INTERNASIONAL PUBLIK DALAM INSTRUMEN DAN PRAKTIK WORLD TRADE ORGANIZATION - Hata, Hata (Sekolah Tinggi Hukum Bandung, 2010)
How does the World Trade Organization relate to the wider corpus of international law ? No straightforward answer can be found in the WTO rules. Yet , as will be shown by the present writer, WTO documents incorporate various rules of general as well as special internationallaw. There are WTO rules that confirm preexisting rules of international law or preexisting treaty law, or deviate from, or even replace preexisting rules of international law. In WTO practices, norms of public international law are frequently invoked before the WTO âjudiciaryâ (Panels and the Appellate Body), and WTO members could clarify or change the relationship between WTO law and other rules of international law. WTO rules are just a partof public international law but in many respect they are lex specialis as opposed to general international law.Keywords: Role of Education - Employment - WTO